“características y efecto biocida de productos vegetales para el control de pseudoperonospora cubensis, en el cultivo de pepinillo (cucumis sativus), en Lamas-San Martín” - Pezo Dávila, Dilmer (2015)
The paper titled Characteristics and Biocidal Effects of plant products for the control of Pseudoperonospora cubensis in cucumber cultivation (Cucumis sativus) in Lamas - San Martín. In order to evaluate the biocidal effect of plant extracts and chemicals comparad to control mildew fungicida on (Pseudoperonospora cubensis) disease affecting the cultivation of gherkin (Cucumis sativus) in the Province of Lamas a test was developed in the horticultura! field "The Pacific" Jorge Luis Pelaez of Rivera, under the design of randomized complete block design (RCBD). We studied 1 O treatments referred to different doses of plant extracts including China Onion, Horsetail, paradise tree, Papaya and Neem and chemicals as Hieloxil Mix 72, Curtine V, Homai W. P. Antracol 70% PM. We evaluated the disease symptoms including the diameter and number of spots on the leaves, allowing to determine the incidence and severity of disease. They also evaluated the diameter, length and weight of the fruits. All plant extracts employees showed biocidal effects reducing leaf area affected and hence increased pathogen (Pseudoperonospora cubensis), both in the upper and middle part of the plant. The extract of Allium fistulosum with 40 mi / I of water showed a lower percentage of leaf spots (between 16% and 27%) followed Equisetum arvense extract 40 mi/ I of water that had 68% efficiency, obtaining greater diameter and length of these fruits. Key Word: Biocides organic downy mildew, Extracts, pathogen.